Online Church Services at GSJA Victorious Worship Family - Kezia Chrestotesia Ingatum; Ronny Juwono (President University, 2021)
To increase the growth of the church members in a church, one aspect that can be done is by introducing the church website application to the church members. Church members can easily get service handling quickly and accurately. It is hoped that the presence of internet media in the church can become an intermediary for information that is easy to access and practical to use so that it helps users find the information they want. This application will provide various functions such as service schedules, congregational data, online consultations, fundraising (if there are church members who need it) and Bible studies. The results of making this website can help users get to know the church where they worship, get the service they want and at the same time feel emotional closeness because they can be served quickly.